2011
DOI: 10.1084/jem.20101629
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived serotonin links vascular disease and tissue fibrosis

Abstract: Blocking 5-HT2B receptor provides a therapeutic target for fibrotic diseases caused by activated platelet release of serotonin during vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
223
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 234 publications
(234 citation statements)
references
References 59 publications
(83 reference statements)
5
223
0
6
Order By: Relevance
“…THP-2 isoform is expressed in central nervous system, whereas TPH-1 is expressed in peripheral tissues such as vascular cells. 45,46 In this study, we provide evidence that TPH1-derived 5-HTP is converted primarily and probably exclusively to 5-MTP in ECs as we do not detect serotonin, melatonin, kynurenine, or by guest on May 11, 2018 http://circres.ahajournals.org/ Downloaded from 5-methoxytryptamine on the metabolomic profile of HUVEC-CM. Our unpublished data reveal that HUVECs express TPH-1 and do not have detectable THP-2.…”
Section: Discussionmentioning
confidence: 57%
“…THP-2 isoform is expressed in central nervous system, whereas TPH-1 is expressed in peripheral tissues such as vascular cells. 45,46 In this study, we provide evidence that TPH1-derived 5-HTP is converted primarily and probably exclusively to 5-MTP in ECs as we do not detect serotonin, melatonin, kynurenine, or by guest on May 11, 2018 http://circres.ahajournals.org/ Downloaded from 5-methoxytryptamine on the metabolomic profile of HUVEC-CM. Our unpublished data reveal that HUVECs express TPH-1 and do not have detectable THP-2.…”
Section: Discussionmentioning
confidence: 57%
“…[26][27][28][29] Older studies identified activated platelets in bronchial biopsies from subjects with asthma, 30 and platelets are essential to the accumulation of eosinophils and the development of inflammation in lungs of allergen-sensitized and challenged mice. 16,31 We initially sought direct evidence for platelet-driven leukocyte recruitment in AERD because of the dramatic tissue eosinophilia that characterizes the disease.…”
Section: Platelet-wbc Adherence Causes Cyslts In Aerd 3795mentioning
confidence: 99%
“…In certain cell types, 5-HT has been identified as a growth factor and has been shown to increase the proliferation of fibroblasts and consequent collagen synthesis that can lead to fibrosis (Fabre et al, 2008). These findings have further been substantiated by Dees et al, (2011) who linked elevated 5-HT levels to vascular disease and tissue fibrosis due to its ability to stimulate extracellular matrix production in both sclerotic and healthy fibroblasts. There are two 5-HT receptor subtypes that have been identified to play an important role in the lungs specifically.…”
Section: Introductionmentioning
confidence: 93%